Effect of light colour temperature on expression and serum profile of selected immune markers in layers - EL-EMAM, H.; ABOU-ISMAIL, U.; EL-ARABY, I.; FOUDA, M.; ATEYA, A. (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was carried out to quantify the effects of different temperatures of light colour on expression and serum profile of selected immune markers in Fayoumi layers. A total of 165 Fayoumi healthy pullets, 17 weeks of age were used. At laying, birds were separated in well ventilated environmentally-controlled rooms and allocated into three groups of 55 birds each (5 males and 50 females) for 3 months and these birds represented the base generation (F0). Fertile eggs were collected and the newly hatched chicks were also divided into three groups from first day of life till 3 months after laying and these represented the first generation (F1). In the two generations, the first group (control) was exposed to cool white LED light (day light) (6500 kelvin), the second group was exposed to very cool white LED light (sky blue light) (10000 kelvin) and the third group was exposed to warm white LED light (yellow light) (2700 kelvin). Birds of each group of the two generations were evaluated for expression profile of TLR4 and IL10 genes and serum level of IL10. Results showed that blue light-exposed groups, in the two generations, exhibited a higher up-regulation of TLR4 and IL10 genes and increased serum level of IL10 compared to groups experienced either white or yellow light colour. Comparison between F0 and F1 individuals revealed improved genetic profiles for F1 birds. The results therefore elucidate the benefits of using blue light in improving the immune status of layers in order to predict the most susceptible risk time for disease incidence and to build up an effective management regimen.